Pengujian Potensi Aktivitas Antibakteri dari Daun Cep-cepan (Saurauia cauliflora DC.) dalam Formulasi Sediaan Gel Terhadap Propionibacterium acnes - Hariyadi Dharmawan Syahputra; Nasri Nasri; Vera Estefania Kaban (Program Studi S1 Farmasi, STIKES Senior, Medan, 2022)
One of the causes of acne is due to a bacterial infection such as Propionibacterium acnes during adolescent puberty. Empirical studies of secondary metabolites contained in Cep-cepan leaves have potential as promising antimicrobials. The main objective of this study was to determine the antibacterial activity of the ethanolic extract of Cep-cepan leaves formulated into a gel preparation against the bacteria Propionibacterium acnes that causes acne. This research method was carried out experimentally where the ethanol extract of cep-cepan leaves was formulated into a gel preparation consisting of (F1) control blank; (F2) 0.5%, (F3) 1%, (F4) 1.5% and positive control (Mediklin). The results of the evaluation of gel preparations at concentrations of 0.5%, 1%, and 1.5% were physically stable during storage at room temperature, homogeneous, and pH. Based on the results of testing the antibacterial activity of gel preparations in inhibiting bacterial growth at a concentration of 0.5% with an average inhibition zone diameter of 11.33 mm, a concentration of 1% with a value of 15.66 mm, a concentration of 1.5% with a value of 19.5 mm. The conclusion of this study is that the ethanol extract of cep-cepan leaves has promising antibacterial activity in the form of a gel formulation.